Emotional arousal and multiple memory systems in the mammalian brain - Packard, Mark G.; Goodman, Jarid (Frontiers in Behavioral Neuroscience, 2012)
Emotional arousal induced by stress and/or anxiety can exert complex effects on learning and memory processes in mammals. Recent studies have begun to link study of the influence of emotional arousal on memory with earlier research indicating that memory is organized in multiple systems in the brain that differ in terms of the “type” of memory they mediate. Specifically, these studies have examined whether emotional arousal may have a differential effect on the “cognitive” and stimulus-response “habit” memory processes subserved by the hippocampus and dorsal striatum, respectively. Evidence indicates that stress or the peripheral injection of anxiogenic drugs can bias animals and humans towards the use of striatal-dependent habit memory in dual-solution tasks in which both hippocampal and stritatal-based strategies can provide an adequate solution. A bias towards the use of habit memory can also be produced by intra-basolateral amygdala administration of anxiogenic drugs, consistent with the well documented role of efferent projections of this brain region in mediating the modulatory influence of emotional arousal on memory. In some learning situations, the bias towards the use of habit memory produced by emotional arousal appears to result from an impairing effect on hippocampus-dependent cognitive memory. Further research examining the neural mechanisms linking emotion and the relative use of multiple memory systems should prove useful in view of the potential role for maladaptive habitual behaviors in various human psychopathologies.